DIFFERENCES EFFECT OF SUPPLEMENT RED GUAVA JUICE WITH RED DRAGON FRUIT JUICE TO INCREASE HEMOGLOBIN AND HEMATOCRIT LEVELS IN POSTPARTUM MOTHER WITH ANEMIA - Barirah; Noor Pramono (Jurnal Penelitian dan Kajian Ilmiah Kesehatan Politeknik Medica Farma Husada Mataram, 2018)
Background: The alternative to prevent anemia in postpartum mothers is to consume fruits with high iron and vitamin C such as red guava fruit and red dragon fruit needed to synthesize hemoglobin and erythrocytes. This study aims to prove that the supplement of red guava fruit juice is more influential compared to red dragon fruit juice on increasing hemoglobin levels, and hematocrit in postpartum women with anemia.Methods: This study used quasy exsperiment method with nonrandomized pretest and posttest design with control group design. The sample technique uses consecutive sampling. The sample consisted of 66 respondents, divided into 3 groups consisting of 22 respondents per group. Results: Results of the study During the 7-day treatment showed in the intervention group red guava fruit juice increased by 2.45 gr/dl for hemoglobin and 11.04% for hematocrit. In the intervention group, red dragon fruit juice was 1.44 gr/dl for hemoglobin and 7.63% for hematocrit. Whereas the control group was 0.79 gr/dl for hemoglobin and 6.63% for hematocrit . Conclusion: Red guava fruit supplementation is more influential in increasing hemoglobin levels and hematocrit in anemia postpartum women who are given Fe tablets compared to red dragon fruit juice